003.3 The prevalence of mycoplasma genitalium and chlamydia trachomatis at various anatomical sites of men who have sex with men in five cities of china. (13th September 2015) - Jiang, J; Liu, P; Cao, NX; Gong, XD
Abstract : Introduction: To determine the prevalence of Mycoplasma genitalium and Chlamydia trachomatis in urethra, rectum and pharynx of men who have sex with men (MSM) in China, and to analyse the association between the agents detection and clinical manifestations. Methods: 388 MSM were recruited at gay bars in five cities of China from September 2007 to November 2008. Rectal and pharyngeal swabs and first void urine were tested for M. genitalium and C trachomatis by PCR. Bivariate and multivariable analyses were performed to determine the association between the infections and clinical manisfestations. Results: The prevalence of M. genitalium infection at urethral, rectal and pharyngeal sites was 17.2% (95% CI: 13.4% to 21.0%), 11.8% (95% CI: 8.4% to 15.2%), and 13.5% (95% CI: 9.9% to 17.1%), respectively. C trachomatis was more commonly detected in rectum (16.0%, 95% CI: 12.2% to 19.8%) than in urethra (9.4%, 95% CI: 6.4% to 12.3%) and in pharynx (0.8%, 95% CI: 0.1% to 1.6%). Urethral M. genitalium infection was significantly associated with urethral discomfort in the past 3 months (AOR: 2.22, 95% CI: 1.09–4.52) and polymorphonuclear leucocyte (PMNL) counts per high-power microscope field (AOR: 2.40, 95% CI: 1.02–5.62). Rectal M. genitalium infection was independently associated with rectal discharge in the past 3 months (AOR: 6.06, 95% CI: 1.59–23.11). For C trachomatis infection, PMNL counts per high-power microscope field (AOR: 4.66, 95% CI: 1.80–12.07) and having receptive anal intercourse with a male in the past 3 months (AOR: 2.27, 95% CI: 1.14–4.54) were associated with urethral and rectal C trachomatis infection, respectively. Conclusion: High prevalence of M. genitalium infection was observed among MSM in China at urethral, rectal and pharyngeal sites. M. genitalium infection was significantly associated with urethral and rectal symptoms. C trachomatis was more commonly detected in rectum and more likely to be asymptomatic. Disclosure of interest statement: No potential conflicts of interest.